ByzRev 08.2026.006: Ayse Çaylak Türker, Byzantine Coins in Çanakkale Museum.: Research into the Early Christian and Byzantine Periods on the Valleys that Reached the Hellespont. Cham: Springer Nature 2025. - Dennert, Martin (The Byzantine Review, 2026)
Ayse Çaylak Türker, Byzantine Coins in Çanakkale Museum. Research into the Early Christian and Byzantine Periods on the Valleys that Reached the Hellespont. Cham: Springer Nature 2025. XI, 298 pp. including 108 plates. – ISBN 978-3-031-99582-8 (print edition); 978-3-031-99583-58 (e-book)